Herbal therapies in gastrointestinal and hepatic disorders: An evidence-based clinical review - Yao, Yongfang; Habib, Murad; Bajwa, Hajra Fazeelat; Qureshi, Anina; Fareed, Rameesha; Altaf, Reem; Ilyas, Umair; Duan, Yongtao; Abbas, Muhammad (Frontiers in Pharmacology, 2022)
GIT and Liver constitute the major organs of the human body. The very survival of the Human body depends on their proper functioning. As the GIT is a huge and complex organ system, the maintenance of proper GIT and Liver health is an arduous task. GIT disturbances like Diarrhea, Stomach Ache, Flatulence, constipation, nausea, and vomiting are very common among a great number of people every day and contribute to a significant burden on the healthcare system. Pharmacies are full of OTC pharmacological drugs to alleviate its common conditions. However, these drugs do not always prove to be fully effective and patients have to keep on living with these ailments without a proper and long-term solution. People have been depending on Herbal Medications for centuries for the treatment of various ailments of GIT, Liver and other organ system problems as well. In recent times, this trend of incorporating Herbal Medication for the treatment of various diseases in both the developing and the developed countries have surged conspicuously. People are using herbal medications; although, substantial data about their efficacy, uses and toxicological effects does not exist. It is indubitable that herbal Medicines have enormous benefits in both the prevention and the treatment of medical ailments, but there are also not without their toxicological effects. It is, therefore, the utmost need of the time that appropriate time, energy, and resources are spent on the development of ethnopharmacology, and herbal products are classified in a pattern similar to Pharmacological Medications with these uses, side effects, mechanism of action and efficacy, etc.